The impact of health literacy on uterine fibroid awareness, diagnosis, and treatment in the United States: a mini literature review - Evans, Joyvina (Frontiers in Reproductive Health, 2024)
Limited health literacy is a social health determinant leading to poor health outcomes. General and health literacy correlate and can impact diagnosis and treatment understanding. Limited literacy can lead to women receiving more significant rates of invasive surgical treatment, including hysterectomies. This review explores the impact of health literacy levels on uterine fibroid awareness, diagnosis, and treatment. PubMed, CINAHL, and Academic Search Premier searched articles published between January 1, 2012, and December 31, 2022. The keywords uterine fibroids, fibroids, myomas, leiomyomas, and health literacy were used. A total of four articles were returned. Increased rates of hysterectomies were found among participants with low income and education, as well as those with limited health literacy. Hysterectomies are the removal of the uterus and thus removes a woman's right to have children. While increased efforts are needed to understand the impact of health literacy levels on disparities and inequities in uterine fibroid diagnosis and treatment, there is still a need for targeted patient education and community-based education that ensures patient understanding of the diagnosis and treatment options for uterine fibroids.